Repurposing the Homeric Epic in Natalie Haynes' A Thousand Ships (2019) and Madeline Miller's Circe (2018) - Petersson,Thea (2024)
Homeric epics have been a continued object of interest across the ages, and it is no different today. Retellings of Greek myths with a focus on the female characters are especially popular with the modern reader. Authors Natalie Haynes and Madeline Miller are two of many who, through their contemporary novels A Thousand Ships (2019) and Circe (2018), have put the focal point on female characters. In this essay, I analyse five motifs from these novels and compare their use in The Iliad and The Odyssey, with the way in which Haynes and Miller participate in Hélène Cixous’ concept of écriture feminine (women’s writing). Drawing on Cixous, I argue that Haynes and Miller repurpose the Homeric epic by rejecting the phallogocentric model that the motifs previously have been associated with. I show how these modern novelists, by using a narrative with a female focal point, enable female characters in Greek myth to reclaim their bodies and have their story told.
Keywords: Modern Retellings; The Iliad; The Odyssey; Greek Mythology; Hélène Cixous; Homeric epic; écriture feminine